Association between perceived partner support and lifestyle in mother-father dyads expecting a first child - Vickà Versele; Vickà Versele; Annick Bogaerts; Annick Bogaerts; Annick Bogaerts; Roland Devlieger; Roland Devlieger; Roland Devlieger; Christophe Matthys; Christophe Matthys; Leonardo Gucciardo; Leonardo Gucciardo; et al. (Frontiers Media S.A., 2022)
BackgroundA healthy lifestyle during pregnancy is important for the health of mother and child. However, unfavorable physical activity (PA) and dietary changes are observed in pregnant women and their partner. Partner's influence on lifestyle has been reported by expectant women and men. The first aim was to analyze associations between perceived partner support on expectant parents own as well as their partner's moderate-to-vigorous intensity PA (MVPA) levels and dietary intake. Secondly, this study aimed to investigate intra-couple associations of MVPA, dietary intake and perceived support.MethodsA total of 152 heterosexual couples were recruited between week 8 and 10 of gestation by means of convenience sampling. Objective anthropometric and 7-day MVPA measurements were performed at 12 weeks of gestation. An online questionnaire was used to assess dietary intake, perceived partner support and socio-demographic characteristics. An Actor-Partner Interdependence Model for distinguishable dyads was constructed to examine the relationship between perceived partner support and both own's (i.e., actor-effect) and the partner's (i.e., partner-effect) MVPA levels, intake of fruits and vegetables, and an "avoidance food group."ResultsFor pregnant women, perceived support from their partner was significantly associated with women's own MVPA levels (i.e., actor-effect; estimate = 0.344, SE = 0.168, p = 0.040) as well as the MVPA levels of the men (i.e., partner-effect; estimate = 0.717, SE = 0.255, p = 0.005). No significant actor- nor partner-effects were found for the expectant fathers. For none of the sexes significant actor-effects were found for fruit/vegetables and "avoidance food group" intake. For pregnant women, there was a positive partner-effect for fruit and vegetable intake (estimate = 7.822, SE = 1.842, p < 0.001) and a negative partner-effect for the "avoidance food group" intake (estimate = −16.115, SE = 3.629, p < 0.001). Positive correlations were found for perceived MVPA support (r = 0.40, p < 0.001), MVPA levels (r = 0.24, p = 0.007) and food intake from the "avoidance food group" (r = 0.28, p = 0.005) between partners.ConclusionThis study shows that male partners can act as significant facilitators for women. Partners may be an important target when promoting MVPA during pregnancy. Additionally, supportive couples seem to strengthen each other in keeping a healthy lifestyle in early pregnancy. These results justify couple-based interventions in the promotion of a healthy lifestyle during the transition to parenthood.Clinical trial registrationClinicaltrials.gov, identifier: NCT03454958.